Estimativa de rendimento e viabilidade econômica da soja irrigada - Basso, Laudenir Juciê (2019)
Water is one of the most important inputs in agricultural production and a determinant of crop productivity. Adequate irrigation management aims the efficiency in water use, providing an increase in the productivity of the water, at the same time that it propitiates economic return to the irrigated areas. Thus, the present study aimed to (a) simulate the soil water balance for different irrigation management strategies by determining the basal crop coefficient (Kcb) and soil evaporation coefficient (Ke), (b) to evaluate the combined effect on soil evaporation (Es) and crop transpiration (Tc) and, (c) to predict grain yield (Y), water productivity (WP), irrigated water productivity (WPI) and economic return (RE) of soybean crop yields for different levels of soil water deficit and product price quotations. The experiment was conducted in an experimental area of the Irriga® System (DER/CCR), at the Federal University of Santa Maria, state of Rio Grande do Sul, Brazil. The study was carried out inside a rainout shelter, whose objective was to control the water deficit applied to the different treatments. The experimental design was fully randomized, with four irrigation management levels, named T80, T70, T60 and T50 (80, 70, 60 and 50% of the total soil available water - TAW, respectively), with three replications. The soil water content was daily measured with a set of FDR (Reflectometry in Frequency Domain) sensors. Morphological characteristics were evaluated during the crop cycle and, at harvest, the yield components were determined. The SIMDualKc model was used to simulate the soil water balance, to calibrate and validate Kcb and Ke coefficients. Statistical results show that the SIMDualKc model was effective in simulating the water balance with values of b0, ranging from 0.96 and 0.99, with a mean square error (RMSE) < 8.30 mm, and PBIAS ranging from 0.90 to 3.65%, which slightly underestimate the ASW values. The initial, mid-season and end-season Kcb were calibrated and validated at 0.15, 1.00 and 0.10, respectively. The Es represented approximately 30% of ETc, due to the absence of surface residues and frequent soil wetting. The results also have shown that the grain yield can be simulated from the Tc, since that the water-yield factor (Ky) is properly calibrated. WPI was higher in T50 treatment, while WP was higher in T80 treatment. The best economic return was found for the T80 and with a sale price of R$ 70.00 per bag of 60 kg, resulting in an ER of R$ 3151.80 per hectare. The T50, on the other hand, when considering a sale price of R$ 50.00 per bag of 60 kg, resulted in a negative economic return of R$ 27.10 per hectare.